2016
DOI: 10.3899/jrheum.160179
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Herpes Zoster Vaccination in Patients with Rheumatoid Arthritis: A Quality Improvement Project

Abstract: Electronic identification of vaccine eligibility and BPA significantly improved HZ vaccination rates. The process required minimal modification of clinic work flow and did not burden the physician's time, and has the potential for self-sustainability and generalizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Out of five studies, three targeted providers and two providers and patients. The number of providers participating in the studies was generally small (8–35) or was not reported ( n = 3 studies) [ 21 , 24 , 25 ]. Patients in the studies ranged from 197 to 3717.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of five studies, three targeted providers and two providers and patients. The number of providers participating in the studies was generally small (8–35) or was not reported ( n = 3 studies) [ 21 , 24 , 25 ]. Patients in the studies ranged from 197 to 3717.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in the studies ranged from 197 to 3717. The identified objective of the intervention was “improving vaccination rates” (in patients) [ 21 24 ], “reducing the frequency of any missed opportunities for vaccination” (in providers) [ 25 ], and “increase the documentation of prescriptions (in providers)” [ 21 , 24 ]. Three studies reported follow-up periods [ 22 , 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations